A Teacher for All Generations : Essays in Honor of James C. VanderKam. - Mason, Eric F. (BRILL, 2011)
These essays honor James C. VanderKam on the occasion of his sixty-fifth birthday and twentieth year on the faculty of the University of Notre Dame. Essays from an international group of scholars address various topics in Second Temple Judaism and biblical studies.